Bone-healing pattern at the surface of titanium implants: An experimental study in the dog - Rossi, Fabio; Lang, Niklaus P.; De Santis, Enzo; Morelli, Fabrizio; Favero, Giovanni; Botticelli, Daniele (Wiley, 2013)
Objective: To study the early sequential stages of osseointegration at implants installed in alveolar bony. Materials and methods: In 12 Labrador dogs, all mandibular premolars and first molars were extracted bilaterally. After 3 months of healing, full-thickness flaps were elevated in the edentulous region of the right side of the mandible. Implants were installed, and the flaps were sutured to allow a fully submerged healing. The timing of the installations in the left side of the mandible and of sacrifices were performed with a schedule that various observation periods to sacrifice from 5, 10, 20, and 30 days were available so that n = 6 was obtained per each healing period. Ground sections were prepared and analyzed. Results: Newly formed bone in contact with the implant surface was found after 10 days of healing and the percentage increased up to 50% after 1 month of healing. A higher percentage was found in the trabecular compared with the cortical bony compartment. Old bone decreased by about 50% during healing, being still present after 1 month (16%). The proportions of bone debris and bone particles were at 27% after 5 days and decreased during healing to 6% after 1 month. Conclusion: Osseointegration (new bone-to-implant contact) developed at various rates for cortical and trabecular compartments, respectively. In the trabecular region, mesenchymal cells were identified, subsequently developing into new bone in contact with the implant surface. In the cortical compartment, however, resorptive processes were observed throughout all periods of healing. The proportion of newly formed bone percentage was lower compared with that of the trabecular area. Old bone was still present after 1 month of healing in both compartments. Bone debris and small bone particles appeared to be involved in initial bone formation. © 2013 John Wiley & Sons A/S.
Keywords: Animal study; Bone; Bone healing; Early healing; Histology; Histometry; Implant dentistry; Osseointegration; Submerged healing